Screening of brinjal varieties resistant to brinjal shoot and fruit borer, Leucinodes orbonalis (Guenee) - Devi, H. Supriya; Singh, K. Mamocha (Indian Journal of Hill Farming, 2019)
The experiment was conducted with sixteen brinjal varieties at College Farm, College of Post Graduate Studies, Barapani under Central Agricultural University, Imphal, Manipur in the year 2014-15 to evaluate their reaction against L. orbonalis. The incidence of Leucinodes orbonalis in shoot was recorded from twenty randomly selected plants in each plot and fruit damages were recorded as number of infested fruit in twenty randomly selected fruit in each plot. All the varieties were infested by L. orbonalis. No significant difference was observed among the different varieties in shoot damage. In fruit damage, green long-183 recorded lowest damage with 7.22 per cent fruit infestation but it was comparable with swarna shyamli (8.89 per cent), navkiran (8.89 per cent) and utsav (9.16 per cent). Highest incidence of 15.6 per cent was recorded in kashi taru.